2021
DOI: 10.1016/j.clae.2021.02.002
|View full text |Cite
|
Sign up to set email alerts
|

BCLA CLEAR – Medical use of contact lenses

Abstract: The medical use of contact lenses is a solution for many complex ocular conditions, including high refractive error, irregular astigmatism, primary and secondary corneal ectasia, disfiguring disease, and ocular surface disease. The development of highly oxygen permeable soft and rigid materials has extended the suitability of contact lenses for such applications. There is consistent evidence that bandage soft contact lenses, particularly silicone hydrogel lenses, improve epithelial healing and reduce pain in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 668 publications
(1,014 reference statements)
0
47
0
9
Order By: Relevance
“…Corneal topography can change with ocular pathology (such as keratoconus) (see CLEAR Medical Uses Report) [129] and affects lens fit more so for rigid corneal lenses (section 4.1). Central corneal radii over a 2− 3 mm radius can be quantified by conventional keratometry, which measures the separation of reflected pair(s) of mires [130].…”
Section: Ocular Surface Topographymentioning
confidence: 99%
See 3 more Smart Citations
“…Corneal topography can change with ocular pathology (such as keratoconus) (see CLEAR Medical Uses Report) [129] and affects lens fit more so for rigid corneal lenses (section 4.1). Central corneal radii over a 2− 3 mm radius can be quantified by conventional keratometry, which measures the separation of reflected pair(s) of mires [130].…”
Section: Ocular Surface Topographymentioning
confidence: 99%
“…Orthokeratology, scleral lenses and medical use of contact lenses have been covered in accompanying reports, so the following sections focus on soft and rigid corneal lenses (see CLEAR Orthokeratology Report and CLEAR Medical Uses Report) [93,129]. Direct evidence based on a patient's history, refractive error and ocular health that informs lens selection is summarised in Table 3.…”
Section: Lens Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparing the effect of autologous serum eye drops with different diluents, several studies have shown that higher concentrations (100%) of serum eye drops provide more benefits than lower concentrations in optimizing tear film stability and reducing symptoms [ 179 , 180 , 181 , 182 ]. Bandage contact lenses, including rigid gas permeable contact lenses, soft hydrogel contact lenses and silicone hydrogel contact lenses, can improve epithelial healing and eliminate chronic irritation in persistent epithelial defects [ 183 , 184 ]. Topical anti-inflammatory drugs, including non-steroidal anti-inflammatory drugs (NSAID) and ophthalmic steroids, play a role in suppressing the initial inflammatory response and in preventing LSCD [ 185 , 186 , 187 ].…”
Section: Therapy Of Lscdmentioning
confidence: 99%